Analyzing User Acceptance of Balindo Paradiso University Information System Using UTAUT 2 Model - Permana, I Putu Hendika; Aristana, I Dewa Gede; Prayana, I Kadek Wira Dharma; Wijaya , Bagus Kusuma; Pratiwi, Ni Wayan Anggita Dara (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
Technological developments in Indonesia are increasing rapidly. With the emergence of Information Technology applications and services such as mobile commerce, it has become common practice for Businesses to utilize Information Technology to facilitate their daily operations in the economy, financial sector, and retail sector. Mobile commerce is becoming popular and increasingly widespread among Indonesian people. Along with the increasingly rapid development of technology, Balindo Paradiso is also taking advantage of technological sophistication by building innovations in the m-commerce sector. This system was created to make it easier for students to access all administrative and financial activities. Students can access the application via smartphone or PC. This research was carried out to find out various aspects that impact students' intentions to use the Balindo Paradiso University Information System. This research is aimed at analyzing aspects that impact student acceptance of the Balindo Paradiso Information system. This research aims to recommend development and improvement to the developers of the Balindo Paradiso Information system in accordance with the research results obtained. The UTAUT 2 theoretical framework was used for this investigation using multiple linear regression tests. The results of the hypothesis test state that the performance expectancy, social influence, habit, and perceived trust variables have a high impact on users' intentions to use the Balindo Paradiso University Information System.